Cerumen: A fundamental but neglected problem by pediatricians. (August 2016) - Marchisio, Paola; Pipolo, Carlotta; Landi, Massimo; Consonni, Dario; Mansi, Nicola; Di Mauro, Giuseppe; Salvatici, Elisabetta; Di Pietro, Pasquale; Esposito, Susanna; Felisati, Giovanni; Principi, Nicola; ,
Abstract: Objectives: Under physiological conditions, cerumen (Ce) is regularly extruded from the ear canal by a self-cleaning mechanism. Failure of this mechanism leads to excessive accumulation or impaction of Ce. Limited data are available concerning the prevalence of cerumen in healthy and sick infants and children. We assessed the prevalence of Ce in a large population of infants and children and compared the Ce removal attitudes of paediatricians (PEDs) and otorhinolaryngologists (ENTs). Methods: Children seen in November 2014 for acute respiratory infections, including suspected acute otitis media, or well-being visits, were enrolled. The following data were recorded: presence, laterality, and amount of Ce; presenting complaints and final diagnosis; attempt to remove Ce during the visit; and type of physician. Results: Among 819 children aged 1 month to 12 years, Ce was present in 594 (72.5%), of whom 478 (80.5%) had bilateral Ce, and 261 (43.9%) had Ce in a relevant amount (cerumen obstructing at least 50% of the ear canal). Presence of Ce was more common in younger and in African or Asian children. PEDs were less likely to remove cerumen than ENTs (28.8% vs 91.0%, p < 0.001) irrespective of age, gender, race and reason for visit. Ce was removed by PEDs in less than one-third of sick children with a final diagnosis of acute otitis media (AOM) (31.6%) compared with almost all the children by ENTs (95.6%, p < 0.001). Conclusion: Ce is highly prevalent in healthy and sick children but is quite neglected by PEDs. Educational programs to reinforce the importance of Ce removal and to improve the techniques for removal in case of suspected AOM should be implemented and rigorously evaluated in order to avoid incorrect diagnosis and erroneous treatments.